A= x-1/x-3 + x-3/x+3 – 4x-12/9-x^2 với x khác 3 và -3 rút gọn

A=
x-1/x-3 + x-3/x+3 – 4x-12/9-x^2 với x khác 3 và -3
rút gọn

2 bình luận về “A= x-1/x-3 + x-3/x+3 – 4x-12/9-x^2 với x khác 3 và -3 rút gọn”

  1. Giải đáp:
    A=(x-1)/(x-3) + (x-3)/(x+3) – (4x-12)/(9-x^2)
    =(x-1)/(x-3) + (x-3)/(x+3) – (4x-12)/((3-x)(3+x))
    =(x-1)/(x-3) + (x-3)/(x+3) + (4x-12)/((x-3)(x+3))
    =((x-1)(x+3))/((x-3)(x+3)) + (x-3)^2/((x-3)(x+3)) + (4x-12)/((x-3)(x+3))
    =((x-1)(x+3)+ (x-3)^2+4x-12)/((x-3)(x+3))
    =(x^2+2x-3+x^2-6x+9+4x-12)/((x-3)(x+3))
    =(2x^2-6)/((x-3)(x+3))
    =(2x^2-6)/(x^2-9)
    Vậy A=(2x^2-6)/(x^2-9) với x\ne±3
    #Kiro
    Lời giải và giải thích chi tiết:
     

    Trả lời

Viết một bình luận

Câu hỏi mới